2015
DOI: 10.1111/famp.12156
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of the Sperm Donor for Heterosexual Couples: Confirming the Position of the Father

Abstract: In the literature, relatively little attention has been paid to the meaning of donor involvement in the intimate couple dyad. The current study aimed to enrich our understanding of couples' meaning-making regarding the anonymous sperm donor and how they dealt with the donor involvement. Semi-structured interviews were conducted with nine couples, who had at least one child conceived through sperm donation. Our thematic analysis showed that the donor conception was seen as a different path to create a normal fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 62 publications
5
22
0
Order By: Relevance
“…This aspect has relevance to account for the fact that both the biological and the non-biological mothers perceived the donor in a shared way. Thoughts and feelings related to the erasure of the donor are consistent with the donor's non-existence reported by previous studies with heterosexual infertile couples (Burr, 2009;Grace et al, 2008;Kirkman, 2004;Wyverkens et al, 2015). However, these findings are new with respect to other studies with female-partnered mothers, as they highlighted only two main patterns of representation, fluctuating from an instrumental presentation to a personification of the donor (Vanfraussen et al, 2001;Wyverkens et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This aspect has relevance to account for the fact that both the biological and the non-biological mothers perceived the donor in a shared way. Thoughts and feelings related to the erasure of the donor are consistent with the donor's non-existence reported by previous studies with heterosexual infertile couples (Burr, 2009;Grace et al, 2008;Kirkman, 2004;Wyverkens et al, 2015). However, these findings are new with respect to other studies with female-partnered mothers, as they highlighted only two main patterns of representation, fluctuating from an instrumental presentation to a personification of the donor (Vanfraussen et al, 2001;Wyverkens et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…It follows that non-biological mothers might experience the donor differently than biological mothers, perceiving him as a threat to their validity as parent. Furthermore, patterns similar to both of these have been found in heterosexual two-parent families (Becker et al, 2005;Grace et al, 2008;Indekeu et al, 2014b;Wyverkens et al, 2015).…”
Section: Comment [Cf1]supporting
confidence: 62%
See 1 more Smart Citation
“…In keeping with this literature, research of a qualitative nature has also indicated that heterosexual couples may minimize the role of the donor in their family narratives ( Becker, 2000 ; Kirkman, 2003 , 2004a , b ; Grace and Daniels, 2007 ; Burr, 2009 ; Wyverkens et al , 2015 ). It has moreover been suggested that single women may be more likely to emphasize the ways in which donors remain present in—rather than absent from—their families, albeit often symbolically ( Graham, 2014 ), and that single mothers may be especially likely to discuss the donor with their children as part of a ‘family reverie’ ( Ehrensaft, 2007 ) in which there exists a ‘fantasy father’ ( Ehrensaft, 2000 ; Hertz, 2006 ).…”
Section: Introductionmentioning
confidence: 93%
“…First, the resulting child will not have a genetic connection with the mother. Although this is not necessarily problematic, it is a suboptimal option for many people, either because they identify parenthood with genetic parenthood (or at least presuppose that one is 'more' of a parent when there is a genetic connection) or because they fear a disruption of their family unit if the donor would claim a role or if the child would regard the donor as the 'real' mother (Wyverkens et al, 2015). Second, oocyte donation requires that a healthy woman is subjected to ovarian stimulation and oocyte retrieval.…”
Section: Self-donationmentioning
confidence: 99%